THE IMPACT OF COVID-19 PANDEMIC TO HEAD AND NECK CANCER CARE IN HASAN SADIKIN HOSPITAL BANDUNG, INDONESIA - DEWI, YUSSY AFRIANI; PERMANA, AGUNG DINASTI; OKTRIVIANTO, DENIS ANUGRAH (International Journal of Pharmacy and Pharmaceutical Sciences, 2021)
Objective: This study represents head and neck cancer patient’s care at Departement of Otorhinolaryngology-Head and Neck Surgery (ORL-HNS) in Hasan Sadikin General Hospital during COVID-19 pandemic. Methods: The study is done using a retrospective descriptive method based on medical record data in patients with head and neck cancer at Oncology Departement of ORL-HNS, Hasan Sadikin General Hospital, Bandung from March to July 2020. Samples were selected with total sampling. All existing subjects who met the study criteria were enrolled. The inclusion criteria in this study were head and neck cancer patients from March to July 2020. The exclusion criteria were incomplete medical records data. Results: The number of outpatient visits at ORL-HNS Departement, Dr. Hasan Sadikin General Hospital Bandung from March to July was 3723 patients with 1796 of them are oncology outpatients. There was a significant decrease in the number of ORL-HNS outpatient in April and May and began to increase steadily in June and July. This is in line with the start of the big-scale social restriction at the end of March and the start of the ‘new normal’ era in early June. Conclusion: The study demonstrates the significant impact of the COVID-19 crisis on oncological care. During COVID-19 pandemic, the treatment of HNC patients has been severely disrupted and caused a decrease in the number of procedures at Dr. Hasan Sadikin General Hospital Bandung.